Influence of Social Media, Influencers, and Word of Mouth on Purchasing Decisions: Bakso Panjul Majalengka - Eli Achmad Mahiri; Engkun Kurnadi; Nia Rosdiana (Penerbit Goodwood, 2026)
Purpose: This study examined the effects of social media marketing, influencers, and word of mouth on the purchasing decisions of Bakso Panjul consumers in Majalengka Regency.Research Methodology: A quantitative survey with descriptive and verification approaches was conducted. Using non-probability accidental sampling and the RAE formula, 100 consumers were selected. Data were analyzed using multiple linear regression with SPSS version 21.Results: The model explained 73.6% of the variance in purchase decisions (R² = 0.736, p < 0.001). Social media marketing, influencers, and word of mouth all had positive and significant effects, with word of mouth showing the strongest influence (? = 0.505), followed by influencer marketing (? = 0.245) and social media marketing (? = 0.227).Conclusion: Social media marketing, influencers, and word of mouth significantly and positively influence consumers' purchasing decisions.Limitations: The study focused only on Bakso Panjul consumers in Majalengka Regency, limiting the generalizability of the findings to other businesses and regions.Contribution: This study contributes to marketing management by confirming the importance of social media marketing, influencers, and word of mouth in shaping consumer purchasing decisions.